GRAMMATICAL ERRORS ANAYLSIS IN WRITING ENGLISH ABSTRACT OF FINAL REPORT AT AIR CONDITIONING AND REFRIGERATION PROGRAMME STUDY OF POLITEKNIK SEKAYU - Alfha Desiana Maria (Esteem Journal of English Education Study Programme, 2020)
Abstract : This research aimed to give clear description and concrete about the students’ ability in writing English abstract of final report at Air Conditioning and Refrigeration Programme Study of Politeknik Sekayu.The ability to write a clear and concise abstract of final report was indispensable skill to writers; thus it was essential for students to be aware of linguistic aspects of writing. This research used secunder data which English abstract of final report written by students’ of at Air Conditioning and Refrigeration Programme Study at Politeknik Sekayu.Thus,  the sample of this research was taken with Simple random sampling, it was a descriptive qualitative research which aimed to analyze grammatical errors. The source of data in this research were documents taken from students’ final report. The data were collected by using coding sheets. The findings of this research showed that the most common grammatical errors found in writing English abstracts of final report were word order with 24%. The possible solutions to overcome students’ grammatical errors were using indirect method in teaching grammar and prioritizing grammar structures to teach. Keywords: grammatical errors, writing English abstract